Efficacy of double-balloon enteroscopy for small-bowel polypectomy: clinical and economic evaluation. (June 2017) - Rahmi, Gabriel; Vinet, Marie-Amélie; Perrod, Guillaume; Saurin, Jean-Christophe; Samaha, Elia; Ponchon, Thierry; Canard, Jean-Marc; Edery, Joël; Maoulida, Hassani; Chatellier, Gilles; Durand-Zaleski, Isabelle; Cellier, Christophe
Background: We evaluated first the feasibility of endoscopic small-bowel polypectomy and second, the economic aspects, by comparing the cost of endoscopic and surgical polyp resection. Methods: A prospective, observational, multicenter study included 494 patients with positive capsule endoscopy (CE) before double-balloon enteroscopy (DBE). We selected only CE with at least one polyp. The retrospective economic evaluation compared patients treated by DBE or surgery for small-bowel polypectomy. Hospital readmission because of repeat polyp resection or complication-related interventions was noted. The 1-year cost was estimated from the viewpoint of the healthcare system and included procedures, hospital admissions and follow up. Results: CE indicated one or more polyps in 62 (12.5%) patients (32 males, 49 ± 5 years), all of whom underwent a successful DBE exploration. The DBE polyp diagnostic yield was 58%. There were no major complications. A total of 26 (42%) patients in the DBE group and 19 (39%) in the control group required hospital readmission. All readmissions in the DBE group were for repeat procedures to remove all polyps, and in the control group, for surgical complications. The total cost of the initial hospitalization (€4014 ± 2239 DBE versus €11, 620 ± 7183 surgery, p < 0.0001) and the 1-year total cost (€8438 ± 9227 DBE versus €13, 402 ± 7919 surgery, p < 0.0001) were lower in the DBE group. Conclusions: Endoscopic polypectomy was efficient and safe. The total cost at 1 year was less for endoscopy than surgery. DBE should be proposed as the first-line treatment for small-bowel polyp resection.